Some possible assessments of the different burial spaces in the Alentejo and Arrábida in prehistory and protohistory - Rocha, Leonor (2015)
Prehistorical and Protohistorical funerary customs appear (or appeared) to have a certain regional variation, depending on the geology and geographical area in which they were found. This outlook has been changing in Portugal in recent years as a result of recent excavations carried out in the Baixo Alentejo, showing that exchanges between the coast and inland areas were not only limited to raw materials but also included ideas and models.